Feminisme dan Stereotip Gender dalam Iklan Produk Kecantikan - Annisa Anindya; Defhany Defhany (Faculty of Social Science, Universitas Negeri Padang, 2019)
Submission of patriarchal cultural ideologies makes inequality in gender identity. The ideology states that gender should have certain characteristics that are perpetuated from time to time. A stereotype of gender identity was formed which was then displayed in various social interactions, including in the mass media, especially advertising. Gender bias, inequality of women's representation, and women objectification are found in advertisements, especially for beauty products. Feminism is the rationale for this study related to the objectification of these women. But this research will explain how women are forever not only objects, but also begin to show themselves as subjects.